Women's Perception Regarding Breastfeeding Support in Workplace: A Scoping Review - Ruqaiyah Ruqaiyah; Nur Anisah Rahmawati; Rahma Winahyu Jannata; Ayatullah Harun; Hadriani Irwan (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: Newborns mostly require breast milk. Women who choose to work are equally responsible for maintaining breastfeeding. Prior studies have identified variations in the time and intensity of breastfeeding before and after returning to work. Disparities exist in the assistance provided for women to breastfeed in the workplace, with past studies revealing insufficient facilities. This study intends to examine women's views on the support for breastfeeding in the workplace.Method: A scoping review was carried out using the PubMed, Google Scholar, and ScienceDirect databases, following PRISMA procedures. The papers were selected based on specific criteria: they had to be cross-sectional and qualitative studies focusing on women's opinions of breastfeeding in the workplace. Additionally, the articles were to be written in English, give the entire text, and have been done between 2019 and 2023.Results: Ten publications were examined from different workplaces. The research examines different forms of work and workplaces. Women's views on breastfeeding support focus on instrumental support, such as inappropriate or unavailable lactation rooms, work hours and policies, lack of breastfeeding groups, facilities for breastfeeding and breast milk pumping, insufficient storage, inadequate childcare facilities, and lack of caregivers at home, which impede exclusive breastfeeding. Emotional support refers to the assistance provided by colleagues in the workplace. Form of information support, namely the absence of communication and information support. There is a common belief that breastfeeding is seen as a personal issue connected to one's knowledge and self-confidence. Cross-sectoral collaboration needs to be involved, including family, workplace commitment, and government support to support the success of breastfeeding in the workplace.